2014
DOI: 10.1002/anie.201310897
|View full text |Cite
|
Sign up to set email alerts
|

Structural Reevaluation of the Electrophilic Hypervalent Iodine Reagent for Trifluoromethylthiolation Supported by the Crystalline Sponge Method for X‐ray Analysis

Abstract: Hypervalent iodine λ3-benziodoxoles are common electrophilic transfer reagents known for their enhanced stability compared to their non-cyclic analogues. Herein we present data showing that chlorobenziodoxole reacts with two different thiolate nucleophiles (thiocyanate and trifluoromethylthiolate), resulting in the formation of stable thioperoxy complexes rather than the expected benziodoxole derivatives. We further report a revised structure for the earlier described electrophilic trifluoromethylthiolation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(111 citation statements)
references
References 51 publications
3
105
0
3
Order By: Relevance
“…We also monitored the reaction of 3a with 2b and (EtO) 2 P(O)H (Figure 3, V), and were able to detect 4a after 3hours,a long with as mall amount of CF 3 SSCF 3 .T his result suggests path A( see Scheme 3) is possible,but not as efficient as path B. Only 19 FNMR data for RSO n CF 3 compounds were found in the literature, [11,28] and no information for CF 3 S(O)H and CF 3 SOH is available.T he 19 FNMR data of related compounds are listed in Table 3f or comparison.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…We also monitored the reaction of 3a with 2b and (EtO) 2 P(O)H (Figure 3, V), and were able to detect 4a after 3hours,a long with as mall amount of CF 3 SSCF 3 .T his result suggests path A( see Scheme 3) is possible,but not as efficient as path B. Only 19 FNMR data for RSO n CF 3 compounds were found in the literature, [11,28] and no information for CF 3 S(O)H and CF 3 SOH is available.T he 19 FNMR data of related compounds are listed in Table 3f or comparison.…”
Section: Methodsmentioning
confidence: 94%
“…[21] CuCl serves as both areducing agent for CF 3 SO 2 Na and also acatalyst for CF 3 SSCF 3 . [11] CF 3 SOH (9) Scheme 3. Proposed mechanism for CF 3 SO 2 Na trifluoromethylthiolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Buchwald and coworkers later demonstrated that the reagent was in fact a thioperoxide. [45] …”
Section: Scheme 13 Dihalogenation and Oxybromination Of Olefinsmentioning
confidence: 99%
“…[8] This provides an anchor for postsynthetic modification (PSM) reactions that occur in the solid state and can be monitored crystallographically. [9][10][11][12][13][14][15] In the absence of an aromatic handle,m atching of the spatial dimension of the pore cavity is also av iable strategy to observe guests using crystallographic methods.This approach has been used to probe photoswitching, [16] change conformational isomerization ratios, [17,18] observe unusual molecular interactions, [19] and identify organic species, [20,21] with the notable advantage of requiring only nanogram to microgram quantities of the analyte.[3]Arange of chemical reactions have been observed within CMFs,i ncluding the conversion of amines into imines, [9,10] Huisgen cycloadditions, [11] Diels-Alder reactions, [14] and metal-catalyzed methylation [12] and bromination.[15] All of these processes occurred upon immersing aC MF that contained am odified intercalated triphenylene moiety into solutions with appropriate chemical reactants.O nly one example of achemical reaction combining gas-phase reagents and aCMF has been reported, and involved the conversion of avinyl group into epoxidation/oxidation products with the aid of ar adical initiator. [14] This reaction, however,r equired loading of the CMF with 2,2'-azobis(isobutyronitrile) and the use of forcing conditions,whereby an emulsion of crystals was heated at 80 8 8Cf or 24 hours in air.T ot he best of our knowledge,a ttempting chemical transformations in CMFs using gas-phase reagents in the absence of solvents is unprecedented.…”
mentioning
confidence: 99%